Genetic Interactions between the Aurora Kinases Reveal New Requirements for AURKB and AURKC during Oocyte Meiosis - Nguyen, Alexandra L; Drutovic, David; Vazquez, Berta N; El Yakoubi, Warif; Gentilello, Amanda S; Malumbres, Marcos; Solc, Petr; Schindler, Karen (Current biology, 2018)
Errors in chromosome segregation during female meiosis I occur frequently, and aneuploid embryos account for 1/3 of all miscarriages in humans [1]. Unlike mitotic cells that require two Aurora kinase (AURK) homologs to help prevent aneuploidy (AURKA and AURKB), mammalian germ cells also require a third (AURKC) [2, 3]. AURKA is the spindle-pole-associated homolog, and AURKB/C are the chromosome-localized homologs. In mitosis, AURKB has essential roles as the catalytic subunit of the chromosomal passenger complex (CPC), regulating chromosome alignment, kinetochore-microtubule attachments, cohesion, the spindle assembly checkpoint, and cytokinesis [4, 5]. In mouse oocyte meiosis, AURKC takes over as the predominant CPC kinase [6], although the requirement for AURKB remains elusive [7]. In the absence of AURKC, AURKB compensates, making defining potential non-overlapping functions difficult [6, 8]. To investigate the role(s) of AURKB and AURKC in oocytes, we analyzed oocyte-specific Aurkb and Aurkc single- and double-knockout (KO) mice. Surprisingly, we find that double KO female mice are fertile. We demonstrate that, in the absence of AURKC, AURKA localizes to chromosomes in a CPC-dependent manner. These data suggest that AURKC prevents AURKA from localizing to chromosomes by competing for CPC binding. This competition is important for adequate spindle length to support meiosis I. We also describe a unique requirement for AURKB to negatively regulate AURKC to prevent aneuploidy. Together, our work reveals oocyte-specific roles for the AURKs in regulating each other's localization and activity. This inter-kinase regulation is critical to support wild-type levels of fecundity in female mice.
Keywords: myši; fertilita; segregace chromozomů; oocyty; Aurora Kinase A; Aneuploidy; aneuploidie; aurora kinasa A; Mice; Animals; Meiosis; zvířata; meióza; Aurora Kinase B; aurora kinasa C; ženské pohlaví; Female; Fertility; Aurora Kinase C; aurora kinasa B; Oocytes; Chromosome Segregation